Premna mollisima Roth. - New Reports for Flora of Maharashtra (India) - Vijay,; Paithane, A.; Bhuktar, Anil S. (Indian Forester, 2013)
Present paper deals with the new record of tree species from the Maharashtra State. During the field survey along the Ellora caves of Aurangabad a specimen of Premna L. was collected and after the critical examination and perusal literature, protologue and type herbarium specimen was identified as Premna mollisima Roth. Which hitherto is known only from Andhra Pradesh, Karnataka and Tamil Nadu is reported first time for flora of Maharashtra. An updated citation, brief description along with photograph is provided for easy identification.